Antioxidant and antimicrobial activities of propolis and açai (Euterpe oleracea Mart) extracts - G.M.S. Gonçalves; N.P. Santos; S.M. Srebernich (São Paulo State University (UNESP), 2011)
Propolis is a natural resin, collected mainly by the honey bee, Apis mellifera, which has been shown to have many biological roles, including antioxidant and antimicrobial effects, both conferred by phenolic compounds, especially flavonoids. The fruit of the açai palm is an important source of anthocyanins, which are also phenolics of the flavonoid group. The aim of this study was to assess the antioxidant and antimicrobial effects of a mixture of propolis and açai extracts. Antimicrobial activity was assessed by BHI broth culture with diluted extract, followed by agar subculture, while antioxidant activity was assessed by the DPPH radical scavenging assay. The results showed that around 2% of the propolis extract showed antimicrobial activity against Staphylococcus aureus and S. epidermidis, while low concentrations of both the ethanolic propolis and aqueous açai extracts, alone and combined, exhibited antioxidant activity. In conclusion, this study showed that the antioxidant effects of propolis and açai were summed in the mixed extracts. Furthermore, this combination would show antimicrobial activity if the minimum inhibitory concentration of propolis extract established in this study were used in the formulation. Hence, these extracts could be mixed into formulations used topically to prevent skin aging and, possibly, disorders caused by microbes, such as acne.